(3QSGdI aj GdLHQs
(3ChdgG (B:s
(3GdMeO ddg GdaJGM aGWQ GdSehGJ hGdCQV CeG HYO aEf GdEeGe GdeMbb YHjO Gddg GdeTghQ HUOQ GdTQjYI PcQ ai GdJhVjM s
(3BNQgG (B:s
(3ef bGd EPG CUHM Gddge Efi CUHMJ efc ai fYeI hYGajI hSJQ aCJe Ydi fYeJc hSJQc hYGajJc ai GdOfjG hGdBNQI KdGK eQGJ EPG CUHM hEPG CeSi cGf MbkG Ydi Gddg Cf jJe Ydjg EfJgGA EPG CUHM hEPG CeSi cGf MbkG Ydi Gddg Cf jJe Ydjg EfJgGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B21s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQg fbhd eNJdaIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs